Designing Tangghe’ Bull Racing to Effort Revitalize Culture Non-Violent Karapan Sapi - Zali, Moh; Selvia Nurlaila; A. Yudi Heryadi; Luluk Ilmiah (UNIVERSITAS ISLAM LAMONGAN, 2025)
The results of the research show that, in the effort to revitalize theTangghe’ bull racing culture, there must be a deliberate attempt toeliminate the stereotype of violence often associated with Karapan Sapicultural events. This can be done by discontinuing the use of rekeng (whips)and by encouraging the government to take firm action in establishingregulations that prohibit the torture and mistreatment of racing bulls.Essentially, Karapan Sapi is a traditional folk celebration held after theharvest season, not a spectacle of cruelty. The study also found that therevitalization efforts in Langsar Village should focus on preserving thesociocultural, socioeconomic, and sociopolitical aspects of the tradition.Moreover, the modern practice of Tangghe’ bull racing should not bereduced to a mere competitive sport, as this could lead to a shift in culturalvalues. The revitalization process must begin with several key stages:preparation, investigation, transformation, regulation, establishment,testing, and implementation. The results indicate a positive response fromthe local community, with the average response score of (4), meaning thatmost people agree with the idea of preserving the Tangghe’ bull racingculture without violence.